Building a successful home staging business : - Schwarz, Barb (John Wiley & Sons, 2007)
For more than thirty-five years, Barb Schwarz—creator of the Home Staging industry and pioneer of the concept—has Staged and sold thousands of homes. During this time, she has also educated well over one million real estate professionals about Staging, and helped more than 12,000 people attain the Accredited Staging Professional (ASP) designation. Now, with Building a Successful Home Staging Business, Schwarz explains how you can set up your own Home Staging business and join the growing legions of creative men and women who are changing the way real estate is marketed and sold.